KEGIATAN REBOISASI PADA LAHAN MIRING UNTUK MENURUNKAN LAJU EROSI DAN SEDIMENTASI - Nurmi, Nurmi; Nurdin, Nurdin; Rahman, Rival; Bahi, Iin Veronica; Dai, Dina Nurdiana (Universitas Negeri Gorontalo, 2025)
This community service aims to reduce the rate of erosion and sedimentation in Tunggulo reservoir by carrying out reforestation tree planting activities around the reservoir located in a sloping topography area. The method used in this community service is to conduct counseling and reforestation tree planting around the reservoir. The benefits of reforestation trees are to increase the cover of vegetation canopies on the soil surface so that it can reduce the rate of erosion and sedimentation. The results of the community service are in the form of transferring research results on reforestation tree planting and maintenance technology. Partners play an active role in this community service, especially in implementing reforestation tree planting in the field. The community service program that was carried out was well received by farmers because the reforestation activities carried out, in addition to preventing soil degradation on sloping land due to low erosion, can also extend the useful life of the reservoir due to minimized sedimentation. Planting was carried out together with local residents and maintenance was continued by residents with monitoring by the community service team to ensure that the reforestation plants could grow and function properly.